Organizing for Sustainable Development: Addressing the Grand Challenges - Federica Angeli; Ashley Metz; Jörg Raab (Routledge, 2022)
The Sustainable Development Goals (SDGs) recognize the increasingly complex, interdependent nature of societal and environmental issues for governments and business. Tackling such "grand challenges" requires the concerted action of a multitude of organizations and multiple stakeholders at different levels in the public, private, and non-profit sector. Organizing for Sustainable Development provides an integrated and comparative overview of the successes and failures of organizational efforts to tackle global societal issues and achieve sustainable development. Summarizing years of study by an interdisciplinary board of authors and contributors, this book provides readers with an in-depth understanding of how existing businesses and new hybrid organizations can achieve sustainable development to bring about an improved society, marking a key contribution to the literature in this field. Combining theoretical views with empirical approaches, the chapters in this book are highly relevant to graduate and undergraduate (multidisciplinary) programs in sustainable development, organization studies, development economics, development studies, international management, and social entrepreneurship.
Keywords: 650; Sustainability; Organizational behaviour; Sustainable development; Grand challenge; Wicked problem; Inclusive business; Corporate social responsibility; Social enterprise; Environmental policy; Company culture; UN; Hybrid Organizations; Responsible Innovation; Impact Investing; Fix Forward; Social Businesses; Social Impact Bonds; Systematic Literature Review Methodology; Bop Strategy; South Sudan; Measurable Social Impact; Bop Market; Logic Tensions; SDG; NGO Sector; Cross-sector Partnerships; Car; Development Management